Cesarean scar pregnancy: scope for hysteroscopy - Shah, Nitin H.; Joshi, Aditi V.; Agrawal, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Scar ectopic pregnancy also known as cesarean scar pregnancy is a rare form of an extrauterine pregnancy. The blastocyst is implanted at the site of the previous cesarean scar. Most patients remain asymptomatic and are detected on routine ultrasonography imaging. The diagnosis and management of this condition is hence challenging and difficult. A timely ultrasonography in the early weeks of gestation is the key to preventing catastrophic events like uterine perforation and excessive hemorrhage. There is a wide armamentarium of treatment modalities to choose from, however each case must be individualised. Medical management has its own limitations and often patients are required to have a long-term follow-up. We present a case of a cesarean scar pregnancy managed conservatively with systemic methotrexate but subsequently requiring surgical intervention done successfully via hysteroscopy. A repeat ultrasonography done a fortnight later revealed no retained products of conception.